2020
DOI: 10.3892/mmr.2020.11656
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MEG3 knockdown alleviates hypoxia‑induced injury in rat cardiomyocytes via the miR‑325‑3p/TRPV4 axis

Abstract: Acute myocardial infarction (AMI) is a common cardiac disease. Long non-coding RNA maternally expressed 3 (MEG3) is associated with cellular processes in numerous complicated diseases, including AMI. However, the mechanism underlying MEG3 in myocardial hypoxia is not completely understood. The present study aimed to investigate the underlying mechanism of MEG3 in myocardial hypoxia. The expression levels of hypoxia-inducible factor 1α (HIF1α), MEG3, microRNA (miR)-325-3p, and transient receptor potential catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…It was reported that miR-325-3p protected the mouse heart after myocardial infarction through inhibiting RIPK3 and programmed necrosis [ 33 ]. LncRNA MEG3 regulates the expression of TRPV4 by phagocytosis of miR-325-3p in sponge, thereby increasing hypoxia-induced myocardial cell injury in rats [ 34 ]. This suggests that miR-325 is involved in right ventricular fibrosis in PAH development.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-325-3p protected the mouse heart after myocardial infarction through inhibiting RIPK3 and programmed necrosis [ 33 ]. LncRNA MEG3 regulates the expression of TRPV4 by phagocytosis of miR-325-3p in sponge, thereby increasing hypoxia-induced myocardial cell injury in rats [ 34 ]. This suggests that miR-325 is involved in right ventricular fibrosis in PAH development.…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxic conditions, transient receptor potential cation channel subfamily V member 4 (TRPV4) expression was significantly increased by competitively binding with miR-325-3p, whereas the effect was reduced by downregulation of lncR-Meg3, indicating a negative feedback loop between lncR-Meg3 and cell survival (Zhou et al, 2021). Knockdown of MEG3 alleviates hypoxia-induced H9c2 cell injury by miR-183-mediated suppression of p27 through activation of PI3K/AKT/FOXO3a signaling pathway (Gong et al, 2018).…”
Section: Lncr-meg3 and Myocardial Infarctionmentioning
confidence: 99%
“…At the same time, after MEG3 inhibition, the expression of the pro-apoptotic gene Caspase-3 was decreased, and the expression of the anti-apoptotic gene Bcl-2 was increased, thus inhibiting myocardial cell apoptosis. 23 Ya Zhao et al demonstrated that MEG3 regulates the expression of Bcl-2 and Caspase-3 proteins through miR-325 3p mediation, negatively regulating the expression of TRPV4 and thus alleviating myocardial cell injury and apoptosis ( Zhou et al, 2021 ). In the study of Bin Yang et al, Bax expression was downregulated in H9C2 cells after oxygen and glucose deprivation (OGD) induction, caspase-3 and Caspase-9 were cleaved, and apoptosis occurred.…”
Section: Lncrna Meg3 Plays a Role In Cardiovascular Diseasementioning
confidence: 99%